CANMAT Guidelines commentary: where does the evidence come from, and how can we use it for our patients?. (22nd January 2013) - Swann, Alan C
Abstract : Swann AC. CANMAT Guidelines commentary: where does the evidence come from, and how can we use it for our patients?  Bipolar Disord 2013: 15: 45–49. © 2013 John Wiley & Sons A/S.Published by Blackwell Publishing Ltd.